The effect of stunting detection and education cards on improving nutritional status of pre-school children - Titih, Huriah; Afifah, Nurul; Yuniarti, Falasifah Ani; Abdul Hamid, Siti Hazariah (AIP Publishing, 2024)
Abstract. Indonesia is the second country with the highest stunting rate in Southeast Asia at 31.8%. In the Special Region of Yogyakarta (DIY), 11.08% of children were short for their age in 2020, which rose to 17.3% in 2021. Detection and health education about stunting are two ways to detect and identify the risks of stunting. This study aimed to know the effect of stunting detection and education cards on improving the nutritional status of preschool-age children. The research used a quasi-experimental design. Respondents to the study included 38 preschool-age children selected into intervention and control groups with purposive sampling techniques. The data was analyzed using the dependent ttest and the independent t-test. This study showed an increase in the z score in the intervention group after being given the stunting detection card program and education intervention. The results showed that most of the respondents in the intervention group had a minimum z score of -2.37 and a maximum of 1.54 after being given the intervention. In contrast, those in the control group had a minimum z score of -2.39 and a maximum of 0.90 after being given the intervention. The results showed a p-value of 0.1720, or p > 0.05. It concluded that there was no difference in the z scores of preschool-aged children in the intervention and control groups after being given a stunting detection and education card.